Seychelles : Interim Performance Update Under the Policy Coordination Instrument-Press Release; and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
COVID-19 has had a severe economic impact on Seychelles through the implementation of strict domestic measures to contain the spread of the virus and the related global spillovers. The authorities have responded with measures to mitigate the economic fallout on businesses and households. To help address the urgent balance of payments need arising from the pandemic, the Executive Board approved on May 8, 2020 the authorities' request for emergency financing under the Rapid Financing Instrument (RFI) of SDR 22.9 million, equivalent to 100 percent of quota (IMF Country Report No. 20/170).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet